Muhammadiyah’s Economic Movement: A Philosophical Perspective From A Systematic Literature Review - Tiara Sekar Harnum; Hanna Hanifa Hira; Zakiah Zakiah; Budi Johan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Muhammadiyah’s economic movement constitutes an important dimension of the organization’s role as a socio-religious movement oriented toward improving the social conditions of the Muslim community. This article aims to systematically analyze how the Muhammadiyah economic movement is developed and implemented within a philosophical perspective. The research employs the Systematic Literature Review (SLR) method by analyzing relevant journal articles. The findings indicate that the Muhammadiyah economic movement is built upon an ideological foundation reflected in the Al-Ma’un theology, the principles of ijtihad and tajdid, and the paradigm of Progressive Islam. This movement is manifested through the socio-economic empowerment of the community, the management of Muhammadiyah Business Ventures (Amal Usaha Muhammadiyah) as an institutional basis, and the development of community entrepreneurship. The review also reveals that Muhammadiyah’s economic movement faces various contemporary socio-economic challenges, which require institutional strengthening and adaptive empowerment strategies. Overall, the findings confirm that the Muhammadiyah economic movement represents a socio-religious practice that integrates Islamic values with institutional engagement and community economic empowerment in responding to modern socio-economic challenges.